An integrated approach for characterizing immunogenic responses toward a bispecific antibody. Issue 1 (1st January 2021) - Cohen, Sivan; Chung, Shan; Spiess, Christoph; Lundin, Victor; Stefanich, Eric; Laing, Steven T.; Clark, Vanessa; Brumm, Jochen; Zhou, Ying; Huang, Catherine; Guerrero, Joyce; Myneni, Srividya; et al.
ABSTRACT: Bispecific antibodies (bsAbs) recognize and bind two different targets or two epitopes of the same antigen, making them an attractive diagnostic and treatment modality. Compared to the production of conventional bivalent monospecific antibodies, bsAbs require greater engineering and manufacturing. Therefore, bsAbs are more likely to differ from endogenous immunoglobulins and contain new epitopes that can increase immunogenic risk. Anti-A/B is a bsAb designed using a 'knobs-into-holes' (KIH) format. Anti-A/B exhibited an unexpectedly high immunogenicity in both preclinical and clinical studies, resulting in early termination of clinical development. Here, we used an integrated approach that combined in silico analysis, in vitro assays, and an in vivo study in non-human primates to characterize anti-A/B immunogenicity. Our findings indicated that the immunogenicity is associated with epitopes in the anti-B arm and not with mutations engineered through the KIH process. Our results showed the value of this integrated approach for performing immunogenicity risk assessment during clinical candidate selection to effectively mitigate risks during bsAb development.